2002
DOI: 10.1210/jcem.87.2.8218
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Hormonal Male Contraceptive Using Testosterone Undecanoate with Oral or Injectable Norethisterone Preparations

Abstract: Suppression of spermatogenesis to azoospermia is the goal of hormonal male contraception based on T combined with gestagens. The combination of the long-acting T, ester testosterone undecanoate (TU), with norethisterone (NET) enanthate (E) showed high efficacy. In the present study, we tested the validity of this approach by varying the NET dose and mode of application. The aim of the study was to achieve high rates of suppression of spermatogenesis as reflected by sperm counts, monitor gonadotropins as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Before the study was initiated, TU had been shown to be well suited for male contraception. In the first hormonal male contraceptive trial applying TU, this ester was given alone or in combination with NETE or LNG and resulted in an azoospermia rate of 7/14, 13/14 and 8/14, respectively (Kamischke et al. , 2001, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Before the study was initiated, TU had been shown to be well suited for male contraception. In the first hormonal male contraceptive trial applying TU, this ester was given alone or in combination with NETE or LNG and resulted in an azoospermia rate of 7/14, 13/14 and 8/14, respectively (Kamischke et al. , 2001, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Sonographic measurements of testes and prostate volumes were performed by applying a high frequency 7.5‐MHz sector scanner as published previously (Kamischke et al. , 2002; Behre & Zitzmann, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There appeared to be no increase in spermatogenic suppression in these two extra study groups, but these subjects did experience a higher degree of possible gestogenic-related side effects from the higher NET doses, including increased nocturnal sweating. All three groups were also subject to apparent androgenrelated side effects of raised haemoglobin, haematocrit and weight [71].…”
Section: Long-acting Combination Regimesmentioning
confidence: 99%